Storyworlds and the semiotic rules of narrative imagination - Keunen, Bart (Primerjalna književnost, 2020)
With the help of Peirce and Cassirer, this article embeds storyworld theory in a broader phenomenology of narrative imagination. A first step is the semiotic description of narrative imagination; storyworld elements come about through the laws that Peirce attributes to all semiotic processes (section 1). Besides, Peirce's insights are used to show that those elements significantly differ according to their phenomenological or epistemological nature. From this description of semiotic processes, a matrix of nine different signs will be derived (section 2) that correspond to nine distinct operations of imagination. The hypothesis is that it suffices to attribute a distinct function to each of the nine signs to adequately describe the experience of a storyworld.
Keywords: Cassirer, Ernst; cognitive theory; domišljija; imagination; kognitivna teorija; Peirce, Charles Sanders; postclassical narratology; postklasična naratologija; pripovedni svet; semiotics; semiotika; story world